PROBLEM/KASUS FAKTOR KUNCI DALAM PROBLEM BASED LEARNING - Wahyuningsih Wahyuningsih (Media Riset Bisnis & Manajemen, 2001)
Problem Based Leaming (PBL) is an approach in leaming systems which confront students against problems of practices orreal-life situations.  This method of leaming will or motivate students to study, to ask, to search, and to discover more and more information / knowledge for problem solving.  Furthermore, the method students will improe their social, communicative and management skills.  There are six types of task / problem in PBL, these are Problem Task, Activity Task, Strategy Task, Application Task, Study Task, and Discussion Task.  The tasks as the learning center should be ill-structured 'messy', often changes with the addition of new information, not solved easily, and does not always result in a 'right answer (open-ended problems).